2019
DOI: 10.1007/s10734-019-00456-7
|View full text |Cite
|
Sign up to set email alerts
|

Excellent researcher or good public servant? The interplay between research and academic citizenship

Abstract: Academics have always been endowed with the privilege of autonomy, but the diffusion of evaluation systems based on publication outcomes potentially jeopardizes the benefits deriving from behaviors that address other pillars of higher education. Besides research and teaching, academic citizenship, i.e., the service behaviors carried out within and outside organizational boundaries, are in fact cornerstones of university functioning. We investigate the relationship between academic citizenship and research afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Finally, a residual model is found in a unique UM (2.9%) that is managed by a distinct entity connected to the university (a foundation). Such variety of ndings is consistent with the option to adopt the more suitable organizational model for managing university collections, provided by the ANVUR (Italian National Agency for the Evaluation of the University and Research System) pursuant Law 240/2010 (so called "Gelmini reform") which introduces managerial logics within the Italian HE systems (Tagliaventi et al, 2020;Veltri & Puntillo, 2020).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, a residual model is found in a unique UM (2.9%) that is managed by a distinct entity connected to the university (a foundation). Such variety of ndings is consistent with the option to adopt the more suitable organizational model for managing university collections, provided by the ANVUR (Italian National Agency for the Evaluation of the University and Research System) pursuant Law 240/2010 (so called "Gelmini reform") which introduces managerial logics within the Italian HE systems (Tagliaventi et al, 2020;Veltri & Puntillo, 2020).…”
Section: Resultssupporting
confidence: 61%
“…Martin & Etzkowitz, 2000) and enable them to meet the social, economic as well as cultural needs of communities (Sataøen, 2018). Therefore, the debate has been focusing on how to assess and reward service activities by academics to encourage them to the advantage of students, collegiate, professionals and civil society (Barker, 2015;Nicolo' et al, 2020;Tagliaventi et al, 2019). Some scholars have referred to the broad concept of university engagement by investigating the service activities by individual academics (Knudsen et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although these criteria may not explain why a candidate was ranked highest, they reflect how evaluation committees select a shortlist of candidates, as they offer a basis for peers' discussions of candidates and the criteria used in arguing for them, even in cases in which this is window dressing (Musselin 2010). Moreover, the emphasis on evaluative criteria sends strong signals to the research community regarding which qualifications are more important than others (Tagliaventi et al 2020), and it has thus been shown to be important in the selection of candidates (Herschberg et al 2018; Van den Brink and Benschop 2011). Hence, we focus on evaluative criteria as more openly expressed factors affecting candidate selection.…”
Section: Evaluative Criteria In Recruitmentmentioning
confidence: 99%
“…They account for approximately one-half of new PhD graduates, one-third of associate professors, but only one-fifth of full professors in both countries. 6 The Spanish and Italian institutional arrangements offer several unique features. In order to be either promoted or hired by a university at the level of associate or full professor, researchers are required to first obtain a qualification granted by a centralized committee at the national level.…”
mentioning
confidence: 99%
“…In Spain, 12 percent of male applicants qualify, gender is not relevant, with the exception of Bagues and Esteve-Volart (2010), who document that female applicants to the Spanish judiciary have lower chances of being hired when they are randomly assigned to an evaluation committee including women. 6 In Italy, women account for 52 percent of new PhD graduates, 36 percent of associate professors, and 21 percent of full professors (Italian Ministry of Education, University, and Research (MIUR) 2016). In Spain, women account for 49 percent of new PhD graduates, 40 percent of associate professors, and 21 percent of full professors (Spanish Ministry of Education, Culture, and Sports (MECD) 2016).…”
mentioning
confidence: 99%